Implementation of Brisk Walking Exercise on Lowering Blood Pressure and Chronic Pain in Hypertension Patients: Implementasi Brisk Walking Exercise Terhadap Penurunan Tekanan Darah dan Nyeri Kronis Pasien Hipertensi - Maritta Sari; Nengke Puspita Sari (Jurnal Riset Media Keperawatan, 2022)
Hypertension is a condition of blood pressure above normal values. Hypertension can be caused by narrowing of the arteries (vasoconstriction) or stiffness of the arteries. Such conditions will increase systemic resistance followed by an increase in blood pressure. This study shows that the positive effect of brisk walking exercise on several cardiovascular diseases is quite a lot. However, there have not been many investigations or reviews that have concluded that it is related to the effectiveness of the model, intensity, duration and frequency of brisk walking in reducing blood pressure in patients with hypertension. The purpose of this study was to review available published data, so that it can be used as scientific evidence to identify the effect of brisk walking exercise on reducing blood pressure in hypertensive patients in terms of model, intensity, duration and frequency. The research methodology used is descriptive research using a design to explore the problem of nursing care at risk of ineffective cerebral perfusion with complementary brisk walking exercise in hypertensive patients using a nursing care approach which includes assessment, nursing diagnosis, nursing intervention, nursing implementation and nursing evaluation. Researchers conducted on 20 patients and compared the response to the results of each action given to 20 respondents then carried out an analysis based on theory and previous research. The results showed that there was a decrease in blood pressure and pain scale in hypertensive patients after the brisk walking exercise was carried out, in respondents the blood pressure decreased from 150/100 mmHg to 130/80 mmHg and the pain scale decreased from a scale of 5 to a scale of 3. Conclusion of Implementation brisk walking which is done with certain procedures can help lower blood pressure in a significant range. Patients with normal conditions and hypertension have different abilities in physical activity, this is a consideration to determine the speed, distance, duration and intensity of brisk walking. Keywords : Hypertension, Brisk Walking Exercise